2016
DOI: 10.3390/ijms17111961
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 Promotes Intraoral Palatal Wound Healing through RAGE-Dependent Mechanisms

Abstract: High mobility group box 1 (HMGB1) is tightly connected to the process of tissue organization upon tissue injury. Here we show that HMGB1 controls epithelium and connective tissue regeneration both in vivo and in vitro during palatal wound healing. Heterozygous HMGB1 (Hmgb1+/−) mice and Wild-type (WT) mice were subjected to palatal injury. Maxillary tissues were stained with Mallory Azan or immunostained with anti-HMGB1, anti-proliferating cell nuclear antigen (PCNA), anti-nuclear factor-κB (NF-κB) p50 and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Normal human oral mucosa is continuously prone to micro-tissue injury. Several recent studies showed the importance of HMGB1 in normal wound healing in vitro and in vivo, including both the skin and oral contexts (25)(26)(27). HMGB1 is shown to strongly influence sterile scar formation (28).…”
Section: Discussionmentioning
confidence: 99%
“…Normal human oral mucosa is continuously prone to micro-tissue injury. Several recent studies showed the importance of HMGB1 in normal wound healing in vitro and in vivo, including both the skin and oral contexts (25)(26)(27). HMGB1 is shown to strongly influence sterile scar formation (28).…”
Section: Discussionmentioning
confidence: 99%
“…Sections of 6 μm thickness were obtained. Mallory’s azan staining was used to visualize collagen fibers, and Mayer’s hematoxylin stain was used to examine the parameters of inflammatory cell infiltration, vasodilation, presence of hemorrhagic areas, edema, ulcerations, and abscesses [ 42 ]. Histopathological sections were analyzed under light microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was performed by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay according to a method previously described [ 42 ]. Briefly, cells were treated with ANT-rich extracts for 1 mg/mL and 5-FU for 1, 5, and 10 μg/mL for 2 days and incubated with MTT (0.5 mg/mL) for 3 h. Formazan crystal was solubilized by adding DMSO for 16 h.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that several receptors are implicated in HMGB1-mediated functions including receptor for advanced glycation end products (RAGE) [19]. Recent studies indicated that HMGB1 promotes intraoral palatal wound healing through RAGE-dependent mechanisms [20]. It is found that HMGB1 enhances recruitment of inflammatory cells to damaged tissues by forming a complex with CXCL12 and the signaling pathway is via CXCR4 [19].…”
Section: Discussionmentioning
confidence: 99%